Influence of methotrexate on infliximab pharmacokinetics and pharmacodynamics in ankylosing spondylitis - Ternant, David (Blackwell Science Inc, 2012)
AIMS: Infliximab, an anti-tumour necrosis factor α monoclonal antibody, has profoundly modified the treatment of several inflammatory diseases. The objective was to assess the influence of methotrexate on the variability of infliximab pharmacokinetics and concentration–effect relationship in axial ankylosing spondylitis (AAS) patients. METHODS: Twenty-six patients with AAS were included in a prospective study. They were treated by infliximab 5 mg kg(−1) infusions at weeks 0, 2, 6, 12 and 18. Infliximab concentrations were measured before, and 2 and 4 h after each infusion, and at each intermediate visit (weeks 1, 3, 4, 5, 8, 10 and 14). Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was measured at each visit. Infliximab pharmacokinetics was described using a two-compartment model with first-order distribution and elimination constants. A population approach was used. Infliximab pharmacodynamics was described using the area under the BASDAI curve. RESULTS: A total of 507 blood samples and 329 BASDAI measurements were collected. The following pharmacokinetic parameters were obtained (interindividual coefficient of variation): volumes of distribution for the central compartment = 2.4 l (9.6%) and peripheral compartment = 1.8 l (26%), systemic clearance = 0.23 l day(−1) (22%) and intercompartment clearance = 2.3 l day(−1). Methotrexate influenced neither pharmacokinetic nor BASDAI variability. CONCLUSIONS: Using the present dosage, the clinical efficacy of infliximab is only weakly influenced by its serum concentrations. The results do not support the combination of methotrexate with infliximab in ankylosing spondylitis.